Regulation and Subfunctionalization of Flowering Time Genes in the Allotetraploid Oil Crop Brassica napus - Schiessl, Sarah (Frontiers in Plant Science, 2020)
Flowering is a vulnerable, but crucial phase in building crop yield. Proper timing of this period is therefore decisive in obtaining optimal yields. However, genetic regulation of flowering integrates many different environmental signals and is therefore extremely complex. This complexity increases in polyploid crops which carry two or more chromosome sets, like wheat, potato or rapeseed. Here, I summarize the current state of knowledge about flowering time gene copies in rapeseed (Brassica napus), an important oil crop with a complex polyploid history and a close relationship to Arabidopsis thaliana. The current data show a high demand for more targeted studies on flowering time genes in crops rather than in models, allowing better breeding designs and a deeper understanding of evolutionary principles. Over evolutionary time, some copies of rapeseed flowering time genes changed or lost their original role, resulting in subfunctionalisation of the respective homologs. For useful applications in breeding, such patterns of subfunctionalisation need to be identified and better understood.